Free Learning To End Educational Feudalism - Regina Mamuko; Sugijanti Supit; Yefta Emor (Institut Agama Kristen Negeri Manado, 2023)
The dominance of culture of feudalism is still inherent inlearning practices in Indonesia. In the context of education, feudalismreflects authoritarian, hierarchical, and centralistic practices in whichteachers or educators are considered a single authority that must berespected without much space for active participation and studentindependence. To respond to this problem, the Indonesian governmenthas launched an initiative known as